Transient facial nerve palsy due to plate and screw removal after sagittal split ramus osteotomy of the mandible - Ryo Wakita; Yukiko Baba; Saki Okabe; Haruhisa Fukayama (Elsevier, 2022)
Facial nerve paralysis (FNP) due to plate removal after orthognathic surgery has not been reported. We describe FNP in a patient who successfully underwent plate/screw removal and genioplasty a year after bilateral sagittal split ramus osteotomy (SSRO). After emerging from general anaesthesia, the right FNP was noticed in the patient. Six hours after infiltration anaesthesia, the patient recovered completely. Although FNP may have been caused by the constituents of the local anaesthetic, we presumed that operation-related transient nerve compression could be the cause of FNP. Careful manipulation is required during plate removal.